2021
DOI: 10.3390/ijerph18063297
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Quitline Characteristics and Smoking Cessation by Educational Attainment, Income, Race/Ethnicity, and Sex

Abstract: Little research examines how tobacco quitlines affect disparities in smoking cessation in the United States. Our study utilized data from the Tobacco Use Supplement to the Current Population Survey (2010, 2011, 2012, 2015, 2018) (TUS-CPS) and state-level quitline data from the North American Quitline Consortium and National Quitline Data Warehouse. We ran multilevel logistic regression models assessing a state-run quitline’s budget, reach, number of counseling sessions offered per caller, and hours of operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Studies conducted in other countries have reported similar findings to our study. Although significant disparities exist in uptake of Quitline in different age, gender, socio-economic and ethnic groups [24,25], initiatives such as tailoring Quitline services, incentivising people who smoke and referrers to use Quitline services can help to effectively address disparities in Quitline use [26,27]. Our study produced evidence that an initiative like '10,000 Lives' can effectively increase the uptake of those programs and reduce the disparities in different population groups.In Australia, referrals to and uptake of Quitline among Aboriginal and Torres Strait Islander peoples are lower than non-Indigenous people.…”
Section: Discussionmentioning
confidence: 78%
“…Studies conducted in other countries have reported similar findings to our study. Although significant disparities exist in uptake of Quitline in different age, gender, socio-economic and ethnic groups [24,25], initiatives such as tailoring Quitline services, incentivising people who smoke and referrers to use Quitline services can help to effectively address disparities in Quitline use [26,27]. Our study produced evidence that an initiative like '10,000 Lives' can effectively increase the uptake of those programs and reduce the disparities in different population groups.In Australia, referrals to and uptake of Quitline among Aboriginal and Torres Strait Islander peoples are lower than non-Indigenous people.…”
Section: Discussionmentioning
confidence: 78%
“…It is possible that quitlines assist in smoking cessation similarly for historically marginalized populations and their nonmarginalized counterparts, but given the additional barriers marginalized communities face to quitting, it might not always translate to sustained smoking cessation. It may be that quitlines are successful in aiding in cessation among populations that are disproportionately impacted by tobacco, 61 although more tailored efforts are needed to close the gap in cessation-related disparities.…”
Section: Discussionmentioning
confidence: 99%